Assessing the proposed association between DED and gluten‐free diet introduction in celiac children. (July 2017) - de Queiroz, Alexandra Mussolino; Arid, Juliana; de Carvalho, Fabrício Kitazono; da Silva, Raquel Assed Bezerra; Küchler, Erika Calvano; Sawamura, Regina; da Silva, Lea Assed Bezerra; Nelson‐Filho, Paulo
ABSTRACT: A strong association between celiac disease (CD) and dental enamel defects (DEDs) have been extensively reported, however, the nature of this relationship is still unclear. The aim of this study was to evaluate DEDs phenotype in CD individuals according to the time they were introduced to a gluten‐free diet (GFD). Forty‐five CD individuals were examined by a pediatric dentist. DEDs were classified according to the type of affected teeth. CD individuals were classified into two groups (with or without DEDs) and the differences between these groups were tested using chi‐square or Fisher´s exact tests and t ‐test to compare differences between means. The Pearson coefficient test was used to evaluate the degree of the correlation between the age of GFD introduction and number of affected teeth. Individuals with MIH were introduced earlier to the GFD ( p = 0.038). An association was also observed for molar DED ( p = 0.013). In conclusion, our study suggested an association between a specific type of DED and the time that CD individuals were introduced to a GFD.